Nutrients management and planting time adaptation to climate change for wet season rice production in subtropical India - Satapathy, Sushree Sagarika; Swain, Dillip Kumar; Pasupalak, Surendranath; Herath, Srikantha (Commonwealth Scientific and Industrial Research Organisation, 2019)
The projected adverse impact of climate change on food grain production of tropical and subtropical latitudes necessitates the development of suitable agro-adaptations. We used open top chamber (OTC) experimental facility and simulation analysis to study the effect of elevated [CO2] with varying nutrients management on rice grain yield and to evaluate planting time adjustment as adaptation to climate change. The OTC experiments with ambient [CO2] level ([CO2] ~390 ppm) and elevated [CO2] (25% higher than the ambient) using cultivar ‘Swarna sub1 (140–145 days)’ were conducted during wet season of the years 2011 and 2012 at West Medinipur, India. Using CERES model, we simulated rice grain yield for future climate scenario (A1B) during the years 2020 (2010–2039) and 2080 (2071–2099) at four selected locations of the subtropical India. The elevated [CO2] in OTC increased panicle number, but decreased filled grain number per panicle, 1000-grain weight and grain yield. The increasing [CO2] had smaller adverse impact for integrated nutrients management as compared with chemical fertiliser. The model simulated grain yield reduction of 6.1−13.0% during 2020 and 14.4 −25.0% during 2080 with rising temperature 1.6 and 4.6°C, respectively, compared with the base period (1961–1990). Early planting during 25 June to 25 July received closure favourable temperature and rainfall during the crop growing period, hence had better adaptation to the climate change. Increasing dose of integrated nutrients and early planting is expected to minimise the adverse impact of climate change on rice production of the subtropical India.